2002
DOI: 10.1063/1.1454197
|View full text |Cite
|
Sign up to set email alerts
|

Interface controlled electrical and magnetic properties in Fe–Fe3O4–silica gel nanocomposites

Abstract: Iron nanoparticles with a shell of Fe3O4 phase with a total diameter of 5.3 nm have been grown within a silica gel matrix in the percolative configuration by suitable reduction followed by oxidation treatments. dc electrical resistivity measurements were carried out in the temperature range 80–300 K. The resistivity of the nanocomposites was found to be about 7 orders of magnitude lower than that of the reference gel. The electrical conduction has been explained on the basis of a small polaron hopping mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 22 publications
2
13
0
Order By: Relevance
“…The activation energy (E a ) of the thermally activated electronic conduction in Fe-silica nanocomposite is found to be 0.59 eV, which is higher than that of Fe-Fe 3 O 4 -SiO 2 gel nanocomposite reported by Das et al [11]. They observed that with an increase in the surface oxidation of the Fe particles, the activation energy of the nanocomposite decreases.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…The activation energy (E a ) of the thermally activated electronic conduction in Fe-silica nanocomposite is found to be 0.59 eV, which is higher than that of Fe-Fe 3 O 4 -SiO 2 gel nanocomposite reported by Das et al [11]. They observed that with an increase in the surface oxidation of the Fe particles, the activation energy of the nanocomposite decreases.…”
Section: Resultsmentioning
confidence: 59%
“…However, Fe particles in nano form have a high affinity for oxygen. Despite the reduction of their total magnetic moment, when dispersed in non-magnetic matrix or coating, several studies have been conducted to encapsulate these particles in silica [1,3], alumina [4], yittria [5,6], gold [7], carbon [8], boron nitride [9], and Fe 3 O 4 [10,11] in order to improve their stability, electrical and magnetic properties. Fe-silica nanocomposites are of particular interest because they have higher resistivity and this combined with the good magnetic properties of metallic Fe, makes them a good candidate for dielectric applications and could possibly be a good replacement material for ferrites.…”
Section: Introductionmentioning
confidence: 99%
“…Metal core-metal oxide shell nanostructures were formed in silica gel matrix. A drastic reduction in electrical resistivity of the nanocomposites was observed as compared to that of the precursor glass [17,18]. This was ascribed to the presence of an interfacial amorphous phase formed by the nanoshell structure.…”
Section: Introductionmentioning
confidence: 76%
“…Another important insulator/conductor transition is related to the temperature and frequency dependence of the electrical parameters such as resistance and dielectric constant [12,13]. Actually, the addition of iron oxide fillers can lead to significant enhancement in the electrical conductivity of the compositions [13].…”
Section: Introductionmentioning
confidence: 99%
“…Actually, the addition of iron oxide fillers can lead to significant enhancement in the electrical conductivity of the compositions [13]. In this paper, the effect of Fe/Si ratio on the electrical and structural properties of heat treated iron oxide nanoparticles embedded in silica matrix prepared by sol-gel method has been investigated.…”
Section: Introductionmentioning
confidence: 99%